2019
DOI: 10.1177/1756286418821918
|View full text |Cite
|
Sign up to set email alerts
|

Human tissue kallikrein in the treatment of acute ischemic stroke

Abstract: Acute ischemic stroke (AIS) remains a major cause of death and disability throughout the world. The most severe form of stroke results from large vessel occlusion of the major branches of the Circle of Willis. The treatment strategies currently available in western countries for large vessel occlusion involve rapid restoration of blood flow through removal of the offending blood clot using mechanical or pharmacological means (e.g. tissue plasma activator; tPA). This review assesses prospects for a novel pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 101 publications
0
18
1
Order By: Relevance
“…In humans, polymorphism in the regulatory region of KLK1 is responsible for significant differences in hK1 expression and susceptibility to systemic hypertension 83, 84 . These findings suggested that KLK1 pathway might be a potential drug target; indeed, recombinant KLK1 treatment has been shown to improve the recovery in acute ischemic stroke by augmenting penumbral blood flow and suppressing inflammation 74 .…”
Section: The New Kids On the Blockmentioning
confidence: 96%
See 1 more Smart Citation
“…In humans, polymorphism in the regulatory region of KLK1 is responsible for significant differences in hK1 expression and susceptibility to systemic hypertension 83, 84 . These findings suggested that KLK1 pathway might be a potential drug target; indeed, recombinant KLK1 treatment has been shown to improve the recovery in acute ischemic stroke by augmenting penumbral blood flow and suppressing inflammation 74 .…”
Section: The New Kids On the Blockmentioning
confidence: 96%
“…KLK1 74 is a component of the kallikrein-kinin system (KKS) implicated in the homeostasis of the cardiovascular, renal and central nervous system 75, 76 . The KKS comprises kallikreins, kininogens, kinins, kinin receptors and kininases (angiotensin-converting enzyme, ACE is the most important kinin-degrading enzyme in the cardiovascular system) 77 .…”
Section: The New Kids On the Blockmentioning
confidence: 99%
“…The inducible expression of KLK1 in RTECs has also been shown to downmodulate local pathological reactions and confer renoprotection in mice with spontaneous LN ( 73 ). Further preclinical studies of KLK1 may support the evaluation of DM199, a recombinant form of human KLK1 currently in acute ischemic stroke clinical trials ( 74 ), for the treatment of LN.…”
Section: Therapeutic Approaches Targeting Rtecs In Lnmentioning
confidence: 99%
“…In the human KLKs family, only KLK1 could release kinin from low molecular weight kininogen, while the other KLKs possess greatly reduced or no kininogen cleavage activity [ 16 ]. KLK1 is a key member of the kallikrein-kinin system that initiates and maintains vasodilation in mammalian system and its deficits are associated with cardiovascular and end-organ pathology [ 18 ]. KLK1 replenishment therapy is widely used in Asia for the treatment of diseases such as acute ischemic stroke [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…KLK1 is a key member of the kallikrein-kinin system that initiates and maintains vasodilation in mammalian system and its deficits are associated with cardiovascular and end-organ pathology [ 18 ]. KLK1 replenishment therapy is widely used in Asia for the treatment of diseases such as acute ischemic stroke [ 18 ].…”
Section: Introductionmentioning
confidence: 99%